Response surface optimization of extraction parameters for enhanced phenolic extraction and antioxidant activity from Cassia fistula flowers - Ganesamoorthy Janarny; Somathilaka Ranaweera; Prasanna Priyantha Gunathilake (International Journal on Food, Agriculture and Natural Resources, 2023)
Cassia fistula is a well-known plant species for the medicinal use of it leaves, barks and flowers. It has been identified as a rich source of phenolics which can be attributed to its medicinal properties. However, these phenolics should be extracted appropriately to effectively utilize them in various applications. This study focused on maximizing the extraction yield of total phenolics and total anthocyanins along with maximum 2,2-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity from edible flowers of C.fistula as a function of solid:liquid ratio, ethanol concentration, extraction temperature and time. The data was subjected to response surface methodology and the corresponding second order polynomial models were generated. The results showed that the polynomial models for all responses were significant, did not show lack of fit and presented determination of coefficients above 95%. This indicates the suitability of the models for prediction purposes. Using desirability function, the optimum extraction process parameters to obtain maximum values of all responses was found to be 29.56% ethanol, 1:45 solid to liquid ratio at extraction temperature of 31°C and time 24 minutes. Under these optimal conditions, the experimental values were in close agreement with the predicted values and did not show any significant difference (p<0.05). The identified optimized conditions could be used to extracts phenolics from C.fistula flowers in a cost effective and efficient manner.